Efecto de varios sustratos sobre la proliferación de plántulas de plátano propagado en cámara térmica - Cobeña Vera, Cristhian Eduardo (2018)
The objective of the research was to evaluate the effect of substrates and combinations of substrates on the proliferation of plantain propagated in a thermal chamber. The experiment was carried out at the Escuela Superior Politécnica Agropecuaria de Manabí “Manuel Félix López”. Substrates rice husk, peanut husk, balsa sawdust and compost were evaluated. Additionally, mixtures of substrates based on rice husk + balsa sawdust, rice husk + peanut peel, rice husk + compost, peanut husk + compost and balsa sawdust + compost were evaluated. A completely randomized design was used, with nine treatments and four replicates, with a total of 36 experimental units. The data was subjected to analysis of variance and the separation of means was made with the Tukey test at 0.05 error probabilities. The main variables evaluated were multiplication rate and number of plants per m2. Prior to the data analysis, the treatment based on rice husk was eliminated, since death of shoots and seedlings was visualized. The results obtained showed that substrates based on balsa sawdust + compost and rice husk + compost showed the highest multiplication rate with 10.70 and 18.81 seedlings per corm. Likewise, the aforementioned substrates showed the highest number of seedlings obtained per m2, with 257 and 403 seedlings in the 90 days that the experiment lasted. The use of compost was determinant in the higher rate of seedling multiplication, independently of the substrate with which it is mixed.